Становление и развитие государственности Удмуртии: монография / В. Ю. Войтович ; рец.: Р. С. Мулукаев, М. И. Шишкин - Войтович Валерий Юрьевич (Удмуртия, 2020)
Экземпляры: КО (2022) / Инвентарный номер: 57950 / Цена: 500.00. / Сис.шифр: К66.3(2Рос.Удм) / Авт.знак: В 65 / ГРНТИ: 11 / ББК: 66.3(2Рос.Удм)